Analysis of Characterization of Physicochemical Properties of Different Formulations of Riceberry Malted Beverage - Parnsakhorn, Sunan; Langkapin, Jaturong (Frontiers in Engineering Innovation Research, 2020)
Rice malt was prepared for beverage production of different three formulations. In three formulations were consisted of malt flour from riceberry, fresh milk and stevia sugar in the ratio 50.0 : 48.5 : 1.5 (Formula 1), 50.0 : 49.0 : 1.0 (Formula 2) and 50.0 : 49.5 : 0.5 (Formula 3) respectively. Each formula was added with 0.1% of gelatin. Then the ingredients were homogenized to mix together. The resulting beverages were analyzed to determine their physicochemical properties include color value, moisture content water activity, anthocyanin content, viscosity, pH value and sensory tests. The results found that the malting process can be divided into three steps, soaking, germination and kilning was effected to decrease of anthocyanin content from 1.94 to 1.17 mg/g dry weight. After that in the production of beverages by mixing with other components, it was found that anthocyanin was presented between 0.17-0.24 mg/ml. While increasing the ratio of fresh milk in beverages was showed increases in overall color difference value ( E*). The viscosity values of three different formulations of riceberry malted beverage were similar ranged between 15.83-17.17 cP. Including their acidity levels 5.5 to 6.0 or classified as a low acidic beverage. Sensory evaluation of the quality attributes of the beverages (color, homogeneity, order, sweetness, flavor, viscosity, and the overall sensory) were revealed that consumers give the highest overall satisfaction in malted beverages made from formula 3. Including the formula 3 was a statistically significant difference (P 0.05) compared to formula 1 and formula 2, which is not significantly different (P> 0.05). This formula that has the lowest the total soluble solids content (TSS) (7oBrix). Moreover, formula 1 and formula 2 were presented the total soluble solids content 9oBrix and 8oBrix, respectively.